2017
DOI: 10.1016/j.breast.2017.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Evolving landscape of human epidermal growth factor receptor 2-positive breast cancer treatment and the future of biosimilars

Abstract: Human epidermal growth factor receptor 2-positive (HER2+) breast cancer comprises approximately 15%-20% of all breast cancers and is associated with a poor prognosis. The introduction of anti-HER2 therapy has significantly improved clinical outcomes for patients with HER2+ breast cancer, and multiple HER2-directed agents (ie, trastuzumab, pertuzumab, lapatinib, and ado-trastuzumab emtansine [T-DM1]) are approved for clinical use in various settings. The treatment landscape for patients with HER2+ breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 106 publications
(155 reference statements)
0
22
0
2
Order By: Relevance
“…Although ERBB2 expression is uncommon in melanomas (www.proteinatlas.org), it appears that high expression levels are caused by amplifications of the genomic locus. In breast and stomach cancers, high ERBB2 levels are associated with rapid tumor growth and metastatic spread and provide the rationale for targeting ERBB2 by treatment with trastuzumab and lapatinib . In a preclinical study of wild‐type BRAF/NRAS but ERBB2‐positive melanoma cell xenografts, it was demonstrated that ERBB2 dimerized with ERBB3, and tumor growth could be reduced significantly in vivo with the ERBB2‐specific antibody pertuzumab …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ERBB2 expression is uncommon in melanomas (www.proteinatlas.org), it appears that high expression levels are caused by amplifications of the genomic locus. In breast and stomach cancers, high ERBB2 levels are associated with rapid tumor growth and metastatic spread and provide the rationale for targeting ERBB2 by treatment with trastuzumab and lapatinib . In a preclinical study of wild‐type BRAF/NRAS but ERBB2‐positive melanoma cell xenografts, it was demonstrated that ERBB2 dimerized with ERBB3, and tumor growth could be reduced significantly in vivo with the ERBB2‐specific antibody pertuzumab …”
Section: Resultsmentioning
confidence: 99%
“…In breast and stomach cancers, high ERBB2 levels are associated with rapid tumor growth and metastatic spread and provide the rationale for targeting ERBB2 by treatment with trastuzumab and lapatinib. 46,47 In a preclinical study of wild-type BRAF/ NRAS but ERBB2-positive melanoma cell xenografts, it was demonstrated that ERBB2 dimerized with ERBB3, and tumor growth could be reduced significantly in vivo with the ERBB2-specific antibody pertuzumab. 48 KIT can be targeted by small-molecule inhibitors, such as imatinib, which are approved for the treatment of gastrointestinal sarcomas with mutations in exon 11, encompassing the juxtamembrane region with amino acids 550 through 591.…”
Section: Resultsmentioning
confidence: 99%
“…TDBs with CD3 affinity in the nanomolar range had increased distribution to secondary lymphatic tissue which may lead to off-target toxicity (Figs. [2][3][4][5]. Previous studies with TDBs that have CD3 affinity in a similar range observed grade Ill-IV toxicity at selected doses within an hour of infusing a folate receptor/CD3-bispecific antibody in ovarian cancer patients, prompted by coating of peripheral T cells with the bispecific antibody and subsequent T-cell activation and cytokine release (27).…”
Section: Discussionmentioning
confidence: 99%
“…Breast cancer is the leading cause of death for women from 20 to 59 years of age diagnosed with any cancer, with approximately 705 new cases diagnosed daily (1). About 15% to 20% of breast cancer overexpress the HER2 and are more likely to invade axillary lymph nodes than other subtypes (2). Approved antibody therapeutics that target HER2 include the monoclonal antibodies trastuzumab and pertuzumab and the antibody-drug conjugate ado-trastuzumab emtansine.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, trastuzumab, pertuzumab, lapatinib, and trastuzumab emtansine (T-DM1) are approved for use in different clinical settings in patients with HER2-positive breast cancer. All of the above inhibit the HER2 pathway, albeit using different strategies [12,13]. Trastuzumab is a recombinant humanized monoclonal antibody that binds the extracellular subdomain IV with internalization and degradation of the HER2 receptor.…”
Section: Introductionmentioning
confidence: 99%